Emerging Inclusion and Diversity Policies in Military Learning Environments: Supporting Organizational Change and Breaking Down the Status Quo - Susan Yelich Biniecki; Paul Berg (Adult Education Research Conference, 2022)
Emerging inclusion and diversity policies within the US military require unique adult education approaches to break down the status quo, facilitate learning for social change, and strengthen force resiliency.
Keywords: military learning; diversity; inclusion